OR07-1EVOLUTION OF TOBACCO INDUSTRY TO SURVIVE IN TOBACCO FREE SOCIETY. (September 2014) - Mochizuki, Y.
Abstract : Since human beings discovered tobacco, series of inventions and innovations for effective and efficient absorption of its most potent psychoactive substance, nicotine, were introduced to the society. The 20th century was called a cigarette century, which created the tobacco industry as one of the most profitable industry through marketing and taxation. However, with the increase of consumption throughout the world, cigarettes had killed 100 million people in the 20th century and it is estimated to increase up to one billion death toll this century. To remedy this global damage, WHO Framework Convention on Tobacco Control entered into force in 2005. Many countries are now enacting new legislation to control tobacco products as well as the tobacco industry. However, during the course of this global trend to make our next generation tobacco free, various products as alternatives to cigarette or even tobacco have been introduced to escape the existing or upcoming regulation over products and industry activities. In this paper, I will demonstrate what's happening in Japan and the world and will discuss how to fill research and policy gaps to confront this situation.